2019
DOI: 10.1021/acs.jpcb.9b01674
|View full text |Cite
|
Sign up to set email alerts
|

Structural Origins of RF3/NaRF4 Nanocrystal Precipitation from Phase-Separated SiO2–Al2O3–RF3–NaF Glasses: A Molecular Dynamics Simulation Study

Abstract: Oxyfluoride glass-ceramics with RF3 or NaRF4 (R3+: rare earth elements) nanocrystals are considered as favorable hosts for luminescence applications. In this work, we utilized large-scale molecular dynamics (MD) simulations with effective partial charge potentials to study a series of oxyfluoride glasses that are of interest to the precipitation of RF3 or NaRF4 nanocrystals as previous experiment results suggested. The results show that phase separation exists in all glass compositions with fluoride-rich regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 68 publications
3
14
0
Order By: Relevance
“…However, the designed molecules were filtered against the protease of SARS-CoV-2 for COVID-19 based on total energy or binding energy (kcal/mol) of drug-target complex using iGEMDOCK Singh et al, 2019;Zhao et al, 2019). Authors, used iGEMDOCK to understand the binding of noscapine and its derivatives with the target to find hit candidation.…”
Section: Target and Ligand Preparationsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the designed molecules were filtered against the protease of SARS-CoV-2 for COVID-19 based on total energy or binding energy (kcal/mol) of drug-target complex using iGEMDOCK Singh et al, 2019;Zhao et al, 2019). Authors, used iGEMDOCK to understand the binding of noscapine and its derivatives with the target to find hit candidation.…”
Section: Target and Ligand Preparationsmentioning
confidence: 99%
“…Authors, used iGEMDOCK to understand the binding of noscapine and its derivatives with the target to find hit candidation. The absorption (% ABS) was calculated using the Equation (1) proposed by Zhao et al (2019).…”
Section: Target and Ligand Preparationsmentioning
confidence: 99%
“…[19,20] Our previous results suggested that www.advancedsciencenews.com www.advtheorysimul.com the fluoride phase separation is a result of the immiscibility nature between the oxide and fluoride network. [21,22] Furthermore, fluoride crystals precipitate from the separated fluoride phase region under certain conditions, [23][24][25][26] meaning that the fluoride crystals have similar composition with the fluoride phase. Therefore, understanding the fluoride phase separation in oxyfluoride glass can not only help to explore the structure-property relationship between the amorphous glass structure and luminescence centers but can also help to predict the possible crystals to be precipitated and to design glass-ceramics with better luminescent properties.…”
Section: Introductionmentioning
confidence: 99%
“…[34] MD simulations with effective pair-wise partial-charge potential have been applied successfully in studying mixed anion glass as well and the results can be compared with the corresponding experiments. [22] Here, in order to understand structural origins of M 1 − x R x F 2 + [22] Here, in order to understand structural origins of M 1 − x R x F 2 +…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation